Utilitarian Model of Resource Allocation in Health Care - Jakutytė, Sigita (Problemos, 2002)
The article discusses the application of utilitarian theory to solve the problem of resource allocation in health care. The first part of the article presents the conception of the principle of utility in health care. In this presentation, the theoretical discussion of this principle is connected with the practical purposes of medicine. The second part of the article discusses utilitarian methodology by specifying the way it is applied to health care. According to this methodology, different ethical and economical categories are considered as commensurable. The article objects to the idea of commensurability and suggests that the application of this methodology doesn’t solve but just simplifies the problem of resource allocation. The third part of the article discusses utilitarian conception of the value of life. The identification of the value of life with its economic value shows some inner inaccuracies of the utilitarian theory. The article discloses the limits of the utilitarian theory in its application to health care.